2018
DOI: 10.1039/c8sc00165k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling destructive quantum interference in tunneling junctions comprising self-assembled monolayers via bond topology and functional groups

Abstract: Three different benzodithiophene derivatives were designed to isolate the effects of bond topology from that of functional groups in quantum interference to examine the role of the quinone functionality separate from cross-conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 71 publications
10
77
0
Order By: Relevance
“…Similar conclusions have been drawn also in somewhat more recent experiments on coupled benzene rings [19]. More recent experimental efforts have even established such subtle correlations like the effects bond topology and electronegativity of atomic sites can have on the degree and the location of QI features in molecular wires [20]. It is suggested that combination of stimuli-response and QI can be an efficient strategy to enhance isomer recognition and conductance switching in single-molecule junctions [21].…”
Section: Introductionsupporting
confidence: 72%
“…Similar conclusions have been drawn also in somewhat more recent experiments on coupled benzene rings [19]. More recent experimental efforts have even established such subtle correlations like the effects bond topology and electronegativity of atomic sites can have on the degree and the location of QI features in molecular wires [20]. It is suggested that combination of stimuli-response and QI can be an efficient strategy to enhance isomer recognition and conductance switching in single-molecule junctions [21].…”
Section: Introductionsupporting
confidence: 72%
“…[9] Constructive QI (CQI) occurs when the interference pattern has al arge amplitude at the point of molecular contact to both the source and drain electrodes,causing high through-molecule conductance.C onversely,d estructive QI (DQI) results in alow amplitude of the propagating electron wave at one or both of the electrode-molecule contacts, causing extremely low through-molecule conductance. [10] The ability to convert between these two scenarios by tuning the molecular pathways can offer an exciting range of opportunities to regulate charge transport through molecules,without changing the molecular backbone structure,l ength, or redox state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Single-molecule electronic junctions have been investigated intensively over the past decade, not only as stepping stones toward functional devices and circuits made from collections of molecules but also because their room-temperature electrical conductance is controlled by quantum interference (QI). [5][6][7][8][9][10][11][12][13][14][15] Figure 1A illustrates an example of a non-classical QI effect, in a graphene-like (anthanthrene) molecular core, when an electrical current is injected and collected via the green arrows, or alternatively, via the red arrows. If the core behaved like a classical resistor network, then the electrical conductance for these two connectivities would be approximately equal.…”
Section: Introductionmentioning
confidence: 99%